Electric current effects in spark plasma sintering: From the evidence of physical phenomenon to constitutive equation formulation. (September 2019) - Lee, Geuntak; Manière, Charles; McKittrick, Joanna; Olevsky, Eugene A.
Abstract: The impact of the electric current on sintering is revealed by introducing the three heating modes during spark plasma sintering enabling the different electric current density flowing into the electrically conductive powders under the same temperature. The experimental evidence of the electric current effect on sintering is demonstrated by the determination of the constitutive parameters obtained from the three heating modes. The enhancement of the dislocation motion and the reduction of the flow stress under the electric current passage are experimentally proven by the ex-situ mechanical strength tests and using the X-ray diffraction results analyzed by the modified Williamson-Hall equation. Graphical abstract: Unlabelled Image